The Postcranial Skeleton of the Lower Jurassic Tritylodon Longaevus from Southern Africa - Gaetano, Leandro Carlos (2017)
Tritylodon longaevus Owen, 1884 is one of the most common members of the Lower Jurassic faunas of the Karoo Basin. The cranial and dental anatomy of this taxon is well known, but its postcranium has not been previously addressed in detail. Our analysis shows that T. longaevus shares many postcranial features with other tritylodontids that distinguish them from other non-mammaliaform cynodonts. The correlation between taxon size and postcranial anatomical traits is briefly explored among tritylodontids, showing that few morphological differences among species correlate with size. Analysis of the purported oldest remains of Tritylodon, from the Norian Los Colorados Formation of Argentina, suggests that they cannot be unambiguously assigned to this taxon, circumscribing the record of Tritylodon to African localities.